2021
DOI: 10.1002/cpz1.102
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Measurements of Sex Hormones in Rodents During Fear Conditioning

Abstract: Fear conditioning (FC) is a widely accepted tool for the assessment of learning and memory processes in rodents related to normal and dysregulated acquired fear. The study of sex differences in fear learning and memory is vast and currently increasing. Sex hormones have proven to be crucial for fear memory formation in males and females, and several methods have been developed to assess this hormonal state in rats and mice. Herein, we explain a routine FC and extinction protocol, together with the evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Determination of the estrous stage in females was performed by assessing vaginal smear cytology [ 27 ]. To assess the phase of the estrous cycle that females presented during the familiarization phase of the NOR, all-female mice were monitored for 3–4 consecutive cycles (approximately 10–14 days) before familiarization to test for regularity of the cycle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of the estrous stage in females was performed by assessing vaginal smear cytology [ 27 ]. To assess the phase of the estrous cycle that females presented during the familiarization phase of the NOR, all-female mice were monitored for 3–4 consecutive cycles (approximately 10–14 days) before familiarization to test for regularity of the cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Metestrus presents a mixture of cornified epithelial cells and a considerable proportion of leukocytes. Diestrus is characterized by > 90% of leukocytes that might present a very small proportion of round nucleated epithelial cells [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the electrophysiology experiment, vaginal swabs were collected for at least 1 week before sacrifice at proestrus, consistent with previous work (6,35). For identification of the estrous cycle stage, vaginal smears were stained using a Shorr stain (Sigma-Aldrich, catalog no.…”
Section: Vaginal Smear Cytologymentioning
confidence: 99%
“…Previous studies have reported sex differences in rodents in the fear memory task [ [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ]. For instance, in context fear conditioning, the freezing level of male rats was significantly higher than that of females, whether the stage was acquisition or extinction [ [42] , [43] , [44] , [45] ].…”
Section: Introductionmentioning
confidence: 99%